Countermeasures Assessment of Liquefaction-Induced Lateral Deformation in a Slope Ground System. (12th February 2013) - Forcellini, Davide; Tarantino, Angelo Marcello
Abstract : Liquefaction-induced lateral spreading may result in significant damage and disruption of functionality for structures and Slope Ground System. In this regard, finite-element simulations are increasingly providing a versatile environment in order to assess economical and effective countermeasures. Several systematic bidimensional FEM computations have been conducted to evaluate mitigation strategies under the action of an applied earthquake excitation. The presented study highlights the potential of computations in providing insights for analysis of liquefaction-induced lateral deformations. In the analysis, some specific assumptions are introduced and verified such as a nine-node quadrilateral elements, massive columns of soil with periodic boundary conditions, and a Lysmer-Kuhlemeyer dashpot used to model the finite rigidity of the underlying elastic medium. Moreover, the study aims to systematically explore the effectiveness of densification as a countermeasure and then evaluate the best extension comparing two scenarios.